HOSPITALIZATIONS FOR DIABETES IN THE NORTH REGION OF MINAS GERAIS - Eva Vitória Freitas Almeida; Alexis Godinho Junior; Giovana Carneiro Malheiro; Laís Montenegro Oliveira; Lorhane Aguiar Araújo; Karina Prince (PsychTech & Health Journal)
Diabetes Mellitus is a group of diseases of the endocrine system in which the body does not produce the hormone insulin, or its use is inefficient. This study aims to analyze the number of hospitalizations for diabetes in the northern region of Minas Gerais from 2011 to 2020. The research universe was based on the SUS Hospital Information System database, referring to the number of hospitalizations, hospital expenses, and patient profiles. The results revealed that from 2011 to 2020, 12,109 hospitalizations for Diabetes Mellitus were recorded in the North of Minas Gerais, averaging 1,211 cases per year, 24.7% of which were in private hospitals, with an average stay of 5.4 days. Most were urgent (99.3%), and expenses totaled BRL 8,552,504.92. As for the mortality rate, there was a reduction from 5.4 to 3.87. There were more hospitalizations in Montes Claros (3,740). However, the mortality rate was higher in Januária (9.3). The disease is predominant in women (52.5%) between 60 and 69 years old (22.0%) and in the mixed race (47.43%), with higher mortality after 80 years of age. Thus, despite the reduction in mortality, hospitalizations remained high, especially in the last years of this study. Therefore, a greater approach to these patterns is essential to mitigate the advance of diabetes mellitus in the region.